Contemporary agrarian question and alternative ways to its solution = Współczesna kwestia agrarna i alternatywne metody jej rozwiązania - Czyżewski, Andrzej; Staniszewski, Jakub (Zielona Góra: Faculty of Economics and Management Press)
Article presents a complex problem of an agrarian question - its causes, consequences and ways of mitigating the negative effects associated with it. Featured, competing models of agricultural development - industrial and sustainable, are characterized. Also the negative effects of excessive industrialization of agricultural production, leading to the failure of this model, are shown.
Keywords: zrównoważone rolnictwo; model rolnictwa industrialnego; Wspólna Polityka Rolna; WPR 2014-2020; sustainable agriculture development model; industrial agriculture model; agrarian question; common agriculture policy; CAP 2014-2020